Near-Infrared Spectroscopy Is Promising to Detect Iliac Artery Flow Limitations in Athletes: A Pilot Study. (20th December 2018) - van Hooff, Martijn; Schep, Goof; Meijer, Eduard; Bender, Mart; Savelberg, Hans
Abstract : Endurance cyclists have a substantial risk to develop flow limitations in the iliac arteries during their career. These flow limitations are due to extreme hemodynamic stress which may result in functional arterial kinking and/or intravascular lesions. Early diagnosis may improve outcome and could prevent the necessity for surgical vascular repair. However, current diagnostic techniques have unsatisfactory sensitivity and cannot be applied during exercise. Near-infrared spectroscopy (NIRS) has shown great diagnostic potential in peripheral vascular disease and might bring a solution since it measures tissue oxygenation in real time during and after exercise. This report describes the first experiences of the application of NIRS in the vastus lateralis muscle during and after maximal graded cycling exercise in ten healthy participants and in three patients with flow limitations due to (1) subtle functional kinking, (2) an intravascular lesion, and (3) severe functional kinking. The results are put into perspective based on an empirically fitted model. Delayed recovery, showing clearly different types of patterns of tissue reoxygenation after exercise, was found in the affected athletes compared with the healthy participants. In the patients that had kinking of the arteries, tissue reoxygenation was clearly more delayed if NIRS was measured in provocative position with flexed hip. In this pilot experiment, clearly distinctive reoxygenation patterns are observed during recovery consistent with severity of flow limitation, indicating that NIRS is a promising diagnostic tool to detect and grade arterial flow limitations in athletes. Our findings may guide research and optimization of NIRS for future clinical application.